Popular folk tales of the Punjab - Aqeel, Shafi (Oxford University Press, 2008)
This collection of Punjabi folk tales was compiled from the narratives of people from various parts of the province of Punjab, Pakistan. These tales form a part of the cultural and literary heritage of the subcontinent of South Asia, a region believed to be the birthplace of folk stories from around the world. They represent the human predilection for telling stories that goes back to the beginning of time. The stories are not the creation of a single individual, but the product of diverse minds embodying the traditions of different ages and the emotions and perceptions of countless generations. Such stories have provided the raw material for all great literature today and the novel, the short story, epic poetry etc., in some form or other, are all indebted to the legacy handed down by word of mouth through thousands of years